Synthesis and Characterization of 1,2,3- Triazole Derivatives from D-Mannitol - Ihmood Kh. Juber (Tikrit Journal of Pure Science)
This research included the use of azido D-Mannitol (3) to synthesize 1,2,3 triazole derivatives. Azido D – Mannitol  (3) itself used as an intermediate which was prepared from reaction of  1, 2:5, 6-Di-o-isopropylidene-3,4-di-p-tosyl-D-Mannitol (2) with sodium azide. The prepared compound (3) was allowed to react with alkenes for the formation of corresponding 1,2,3 triazole (4a-e ).